Prognostic value of right ventricular systolic function by speckle tracking echocardiography beyond conventional echocardiography in significant tricuspid regurgitation. (25th November 2020) - Hinojar Baydes, R; De Angelis, V; Garcia-Martin, A; Gonzalez-Gomez, A; Sanroman, M; Pascual, M; Lorente, A; Monteagudo, J.M; Jimenez-Nacher, J.J; Zamorano, J.L; Fernandez-Golfin, C
Abstract: Background: Right ventricular (RV) systolic function is determinant in the evaluation of patients with significant tricuspid regurgitation (TR). Timely detection of RV dysfunction with conventional 2D echocardiography is limited by the geometry and position of the RV. RV strain has emerged as an accurate and sensitive tool for evaluation of RV function with the capability of detect subclinical RV dysfunction Purpose: This study was aimed to evaluate the prognostic value of RV strain in consecutive patients with significant TR, in comparison with conventional parameters of RV systolic function. Methods: Consecutive patients in stable clinical status with significant TR (severe, massive or torrential TR) evaluated in the Heart Valve Clinic were included. RV systolic function was measured with conventional echocardiographic parameters (RV fractional area change [FAC], tricuspid annular plane systolic excursion [TAPSE]), DTI S wave ('S) and with STE derived automatic peak global and free wall longitudinal strain (GLS, FW-LS respectively) using the EPIQ system. A combined endpoint of hospital admission due to heart failure or cardiovascular mortality was defined. Results: A total of 100 patients were included (mean age was 76±10 years, 65% females, 84% in NYHA I/II, 86% functional TR). Mean values of RV function parameters are shown in the table. During a mean follow up of 24±10 months, 24% of the patients reached the combined endpoint. Patients with events showed impaired RV GLS and FW-LS (p<0.01). Both parameters were predictive of the combined endpoint (table 1). Conventional parameters of RV systolic function were not associated with outcomes (p>0.05 for all). Conclusion: In patients with severe TR, RV strain values are superior to conventional parameters to detect RV dysfunction. Among different measurements of RV function, RV GLS and FW-LS were the only predictors of poor prognosis. These parameters should be included in the serial evaluation of these patients. Funding Acknowledgement: Type of funding source: None